ANALYSIS OF EATING DISORDERS IN PEOPLE WITH PRIMARY OBESITY - Tykhonova, T.M.; Vasylenko, O.O.; Barabash, N.Y.; Al-Trawneh, O.V. (World of Medicine and Biology, 2025)
The study analysed eating disorders in people with primary obesity. 91 patients with primary obesity of varying degrees were involved in the study. The analysis of eating behaviour was carried out using the Dutch Eating Behavior Questionnaire for assessment of restricted, emotional and external eating behaviour, which helps to identify these pathological types of eating behaviour. It was found that the emotional eating disorder was present only in women. In isolation or combination with other options, the restrictive type of eating disorder was most often detected, and is significantly more often recorded in young people, as well as the external type. In 36.26 % of the examined patients, the presence of all three types of eating disorders was established. The absence of eating disorders was found in 13.19 % of the surveyed. In our opinion, the obtained data justify the need for complex treatment of patients with primary obesity with the involvement of a psychotherapist, because the effectiveness of the measures depends not only on the appropriate correction of lifestyle and the prescription of adequate drug therapy, but also to a large extent on the patient’s awareness of their eating disorders.